2020
DOI: 10.3390/ijms21176292
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel Potentiates the Anticancer Effect of Cetuximab by Enhancing Antibody-Dependent Cellular Cytotoxicity on Oral Squamous Cell Carcinoma Cells In Vitro

Abstract: Administration of cetuximab (C-mab) in combination with paclitaxel (PTX) has been used for patients with head and neck squamous cell carcinoma (SCC) clinically. In this study, we attempted to clarify the molecular mechanisms of the enhancing anticancer effect of C-mab combined with PTX on oral SCC cells in vitro. We used two oral SCC cells (HSC4, OSC19) and A431 cells. PTX alone inhibited cell growth in all cells in a concentration-dependent manner. C-mab alone inhibited the growth of A431 and OSC19 cells at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Panitumumab, a complete human IgG2 antibody, is effective for colorectal cancer, but not for head and neck cancers, including oral cancer [ 24 ]. We have recently suggested that the main action of cetuximab in oral cancer may be immunological reaction, such as ADCC, rather than signaling blockade [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Panitumumab, a complete human IgG2 antibody, is effective for colorectal cancer, but not for head and neck cancers, including oral cancer [ 24 ]. We have recently suggested that the main action of cetuximab in oral cancer may be immunological reaction, such as ADCC, rather than signaling blockade [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…cetuximab is an antibody to epidermal growth factor receptor (EGFR) that is used for treatment of metastatic colorectal cancer, metastatic non-small cell lung cancer, and head and neck cancer. We have suggested that the main effect of cetuximab in patients with OSCC may be immunological, such as antibody-dependent cellular cytotoxicity (ADCC), rather than signaling blockade [ 11 ]. In OSCC patients with local recurrence, lymph node metastasis, or distal metastasis, we hypothesized that dormant cancer cells that could not be detected before or during initial treatment might grow after the primary treatment and develop into a visible tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PTX is often used as an adjunct drug to other anticancer drugs in the treatment of OSCC. For example, PTX enhanced the toxicity of cetuximab to OSCC cells and induced apoptosis of OSCC cells [ 47 ]. However, the use of chemotherapeutic agents in OSCC is limited by the development of intrinsic or acquired drug resistance in patients.…”
Section: Overview On Oscc and Chemoresistancementioning
confidence: 99%
“…It competitively inhibits binding of the epidermal growth factor and tumor growth factor-alpha, by which it reduces tumor growth, and cancer cell migration and spreading. Antibody-dependent cellular cytotoxicity, the main mechanism of anticancer action of cetuximab, can be further increased by paclitaxel [ 148 ]. Co-administration of cetuximab and paclitaxel was reported to be effective not only for the treatment of head and neck carcinoma but also for cervical, esophageal, urothelial, or non-small cell lung carcinoma, on which there are currently active clinical trials [ 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 ].…”
Section: Introductionmentioning
confidence: 99%